2022
DOI: 10.3390/ijms23042173
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis and Genomic Prediction of Thyroglobulin Plasma Levels

Abstract: Thyroglobulin (Tg) is an iodoglycoprotein produced by thyroid follicular cells which acts as an essential substrate for thyroid hormone synthesis. To date, only one genome-wide association study (GWAS) of plasma Tg levels has been performed by our research group. Utilizing recent advancements in computation and modeling, we apply a Bayesian approach to the probabilistic inference of the genetic architecture of Tg. We fitted a Bayesian sparse linear mixed model (BSLMM) and a frequentist linear mixed model (LMM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…Genome-wide association studies (GWAS) commonly used to unravel the genetic basis of polygenic disorders were used in research on thyroid-cancer-specific germline variants [8][9][10][11][12][13][14][15][16][17][18]. Our recent GWAS identified that the gene encoding for ST6 beta-galactoside alpha-2,6-sialyltransferase 1 (ST6GAL1) was associated with plasma thyroglobulin (Tg) levels [19] and the result was confirmed in the replication study of our research group after including over a thousand new individuals, emphasizing that ST6GAL1 significantly contributes to the variation of Tg plasma levels [20].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Genome-wide association studies (GWAS) commonly used to unravel the genetic basis of polygenic disorders were used in research on thyroid-cancer-specific germline variants [8][9][10][11][12][13][14][15][16][17][18]. Our recent GWAS identified that the gene encoding for ST6 beta-galactoside alpha-2,6-sialyltransferase 1 (ST6GAL1) was associated with plasma thyroglobulin (Tg) levels [19] and the result was confirmed in the replication study of our research group after including over a thousand new individuals, emphasizing that ST6GAL1 significantly contributes to the variation of Tg plasma levels [20].…”
Section: Introductionsupporting
confidence: 65%
“…The strength of our current study is that we analyzed the ST6GAL1 protein expression in different types of well-differentiated thyroid cancers. We decided to conduct this study since our previous GWA studies showed that certain variants of the ST6GAL1 gene were associated with plasma Tg levels [19,20]. Tg is the most abundant protein in the thyroid gland that releases thyroid hormones by proteolysis [39] and has increased plasma levels in thyroid pathology [40].…”
Section: Discussionmentioning
confidence: 99%